Introducing HIV and aids education into the first year of a problem-based learning curriculum: a template for health science education - Michelle McLean; Linda Hiles (AOSIS, 2005)
The HIV and AIDS epidemic will continue to impact medically, socially and financially on sub-Saharan Africa. Opsomming Die MIV/VIGS-epidemie sal voortduur om 'n mediese, sosiale en finansiële impak op Afrika, suid van die Sahara, te maak. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.